Nanopatterning with Photonic Nanojets: Review and Perspectives in Biomedical Research - Surdo, Salvatore (Micromachines (Basel), 2021)
Nanostructured surfaces and devices offer astounding possibilities for biomedical research, including cellular and molecular biology, diagnostics, and therapeutics. However, the wide implementation of these systems is currently limited by the lack of cost-effective and easy-to-use nanopatterning tools. A promising solution is to use optical methods based on photonic nanojets, namely, needle-like beams featuring a nanometric width. In this review, we survey the physics, engineering strategies, and recent implementations of photonic nanojets for high-throughput generation of arbitrary nanopatterns, along with applications in optics, electronics, mechanics, and biosensing. An outlook of the potential impact of nanopatterning technologies based on photonic nanojets in several relevant biomedical areas is also provided.